Real Exchange Rate Uncertainty and Private Investment in Developing Countries - Servén, Luis (World Bank, Washington, D.C., 2013)
The author examines empirically the link between real exchange rate uncertainty and private investment in developing countries using a large cross country-time series data set. He builds a GARCH-based measure of real exchange rate volatility and finds that it has a strong negative impact on investment, after controlling for other standard investment determinants and taking into account their potential endogeneity. The impact of uncertainty is not uniform, however. There is some evidence of threshold effects, so that uncertainty only matters when it exceeds some critical level. In addition, the negative impact of real exchange rate uncertainty on investment is significantly larger in economies that are highly open and in those with less developed financial systems.